NILAI-NILAI ISLAM WASATHIYAH DALAM MEWUJUDKAN MODERASI BERAGAMA PADA MASYARAKAT SEKOLAH MULTIKULTURAL - Iffah Rosyidah; Friendis Syani Amrulloh (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The recent rise in cases of intolerance and discrimination regarding religious dress regulations in secular and multicultural educational environments is the background to this research. These socio-religious issues demand the reconstruction of a friendly religious paradigm to reduce extreme fanaticism. The focus of this research is to explore the strengthening of Islamic wasathiyyah values ​​in realizing religious moderation in multicultural school ecosystems. The research steps were carried out using a qualitative approach with a library research method published in the last five years. Secondary data collection was systematically collected through a search of regulatory documents, empirical cases, and theological literature, which were then analyzed using descriptive-analytical techniques with an interactive model through the stages of data reduction, data presentation, and conclusion drawing. The research findings indicate that the internalization of Islamic wasathiyyah values ​​into teaching materials and classroom discussions has proven effective in breaking down the walls of sectarian prejudice within the school community. This principle of moderation has a positive impact in the form of an inclusive space for ethnic diversity without harming students' personal religious beliefs. The main conclusion confirms that the implementation of the three main pillars of wasathiyyah (modesty), namely tawasuth (consideration), tawazun (respect), and tasamuh (compassion), has successfully served as the foundation for character education in realizing substantive multicultural harmony. This synergy positions schools as social wombs, producing learning agents who are steadfast in their faith and adaptive in respecting the religious rights of others. ABSTRAK Maraknya kasus intoleransi dan diskriminasi regulasi busana keagamaan di lingkungan pendidikan sekuler dan multikultural belakangan ini melatarbelakangi penelitian ini. Masalah sosioreligius tersebut menuntut adanya rekonstruksi paradigma beragama yang ramah guna mereduksi fanatisme ekstrem. Fokus penelitian ini adalah mengeksplorasi penguatan nilai-nilai Islam wasathiyyah dalam mewujudkan moderasi beragama di ekosistem sekolah multikultural. Langkah-langkah penelitian dijalankan menggunakan pendekatan kualitatif dengan metode studi kepustakaan (library research) terbitan lima tahun terakhir. Pengumpulan data sekunder dihimpun secara sistematis melalui penelusuran dokumen regulasi, kasus empiris, dan literatur teologis, yang kemudian dianalisis menggunakan teknik deskriptif-analitis model interaktif melalui tahapan reduksi, penyajian data, serta penarikan kesimpulan. Temuan penelitian menunjukkan bahwa internalisasi nilai Islam wasathiyyah ke dalam materi ajar dan diskusi kelas terbukti efektif meruntuhkan tembok prasangka sektarian warga sekolah. Prinsip moderasi ini memberikan dampak positif berupa ruang inklusif bagi keberagaman etnis tanpa mencederai keyakinan akidah pribadi siswa. Simpulan utama menegaskan bahwa implementasi tiga pilar utama wasathiyyah, yaitu tawasuth, tawazun, dan tasamuh, sukses menjadi fondasi pendidikan karakter dalam merealisasikan kerukunan multikultural yang substantif. Sinergi ini memosisikan sekolah sebagai rahim sosial untuk melahirkan agen pembelajar yang teguh beriman sekaligus adaptif menghargai hak beragama orang lain.